A phase II study of induction PD-1 blockade (nivolumab) in patients with surgically completely resectable mismatch repair deficient endometrial cancer (NIVEC) - Lee, Yong Jae; Lee, Yoo-Young; Park, Jeong-Yeol; Cho, Hyun-Woong; Lim, Myong Cheol; Kim, Mi Kyung; Lee, Jong-Min; Lee, Jung-Yun (Journal of gynecologic oncology, 2025)
Mismatch repair deficient (MMRd) tumors are known to be highly immunogenic and of great interest for immune checkpoint inhibitor. However, there is no data about the complete response (CR) rate of programmed cell death protein 1 (PD-1) blockade and surgery in subjects with MMRd surgically resectable endometrial cancer. In this regard, we suggest a window of opportunity study of induction PD-1 blockade (nivolumab) in patients with surgically resectable MMRd endometrial cancer. This is a multicenter, single-arm phase II trial. A total of 30 surgically resectable MMRd endometrial cancer patients will be enrolled. Inclusion criteria include clinical stage I-IIIC2, tumor specimen that demonstrates MMRd by immunohistochemistry or microsatellite instability. Exclusion criteria include multiple primary cancers, residual adverse effects of prior therapy or effects of surgery. Patients are treated with nivolumab 480 mg intravenously every 4 weeks up to 6 months followed by standard surgery and/or adjuvant treatment. The primary endpoint of the study is clinical CR rate or pathological CR rate after treatment of nivolumab. Secondary endpoints include objective response rate, progression-free survival, overall survival, and adverse events. Correlative studies include genomic characterization of tumors, assessment of immune infiltration of tumor microenvironment, and serial circulating cell-free DNA and immune biomarkers. ClinicalTrials.gov Identifier: NCT05795244.